New media, new advertisers a critical discourse analysis on Filipino beauty Tiktok content - Marcelo, Kriscia Anne Sabino; Tañaquin, Annicalou C. (Quezon City College of Mass Communication, University of the Philippines, 2023)
This study uses the Political Economy as a framework to understand why beauty TikTok content can persuade its viewers to buy beauty products and promote consumerism among its audiences. Using Fairclough's Three-Dimensional Critical Discourse Analysis as a theory and method, I subjected 20 existing Beauty TikTok Content of Filipino TikTok creators with product mention to textual analysis. I interviewed three beauty TikTok influencers and facilitated a focus group discussion of beauty TikTok viewers for processing analysis. Through social analysis, I investigated the context of beauty TikTok content's production, consumption, and distribution. This study contributes to the limited research on TikTok and understands the platform through the lens of the Political Economy. I uncovered the language and strategies prevalent in the Filipino beauty TikTok community to help viewers realize the impetus of their purchasing decisions and create informed consumers who know when they are being exposed to advertisements.

Keywords: TikTok, Beauty TikTok Content, Political Economy, Critical Discourse Analysis
Ang pananaliksik na ito ay gumagamit ng critical discourse analysis sa pag-aanalisa ng mga Beauty TikTok video na tungkol sa pagpapaganda partikular sa mga video na nagbabanggit ng mga brands ng makeup at skincare. Ginamit ang teorya ng Political Economy upang unawain ang pagiging epektibo ng mga Beauty TikTok video sa pag-halina ng mamimili. Gamit ang three-dimensional design ng Critical Discourse Analysis ni Fairclough hilang teorya at metodo, inalisa ko ang 20 Beauty TikTok videos na nagbabanggit ng mga produktong pampaganda sa textual analysis, nakipanayam ako sa 3 beauty TikTok content creator at nagpasinaya ng Focus Group Discussion ng mga manonood ng beauty TikTok content para sa processing analysis, at inimbestigahan ko ang konteksto ng produksyon, pagkonsumo, at distribusyon ng beauty TikTok content gamit ang social analysis. Layunin ko na umambag sa limitadong pag-aaral tungkol sa TikTok at tingnan ang social media application sa lente ng Political Economy. lsiniwalat rig pananaliksik na ito ang mga salita at estratehiya ng Filipino beauty Tiktok Content community na siyang dahilan kung bakit madali silang mahikayat ng mga TikTok video na bumili ng mga produktong pampaganda. Layunin ng pananaliksik na ito na lumikha ng maaalam na TikTok users na may kakayanang makita ang mga pagkakataon na sila ay inilalantad sa patalastas.

Mga Susing Salita: TikTok, Beauty Tiktok Content, Political Economy, Critical Discourse Analysis
Vita.
Thesis
Includes bibliographical references and appendices.
Keywords: Social media—Influence.; Internet personalities -- Philippines; Mass media and business -- Philippines